α6 nAChR subunit residues that confer α-conotoxin BuIA selectivity - Kim, Hyun-Woo (Federation of American Societies for Experimental Biology, 2012)
Nicotinic acetylcholine receptors (nAChRs) containing α6 and/or α4 subunits modulate the release of dopamine. However, few compounds can effectively discriminate between ligand-binding sites that contain α6 vs. α4 nAChR subunits. Using a chimeric (α6/α4) subunit, we showed that α-conotoxin BuIA binds the extracellular rat α6β2 vs. α4β2 interface with ∼60,000-fold selectivity. Chimeras containing residues from the α6 subunit were inserted into the homologous position of the α4 subunit to identify critical sequence segments. The region between residues 184 and 207 in the α6 subunit accounted for the potency difference. Chimeras within this region followed by point mutations were constructed for further definition. α6 Lys185, Thr187, and Ile188 form a triad of key residues that influence BuIA binding; when these 3 α6 residues were inserted into the α4 subunit, there was an ∼2000-fold increase in toxin potency. We used a crystal structure of BuIA bound to the acetylcholine-binding protein together with the structure of the Torepedo marmorata nAChR to build a homology model of BuIA bound to the interface between α6 and β2 subunits. The results indicate that the triad of α6 residues lies outside the C loop and is distantly located from bound BuIA (>10 Å). This suggests that alterations in potency are not caused by the direct interaction between the triad and BuIA. Instead, alterations in C-loop 3-dimensional structure and/or flexibility may account for differential potency. Thr198 and Tyr205 also contributed to BuIA potency. In addition, Thr198 caused BuIA potency differences between the closely related α6 and α3 subunits. Together, the findings provide insight into differences between the α6 and other α subunits that may be exploited by α-conotoxins to achieve binding selectivity.—Kim, H.-W., McIntosh, J. M. α6 nAChR subunit residues that confer α-conotoxin BuIA selectivity.